A DESCRIPTIVE STUDY ON THE USABILITY (COHERENCE AND COHESION WITH THE CURRICULUM) OF SOME MODULES: ENGLISH ON SKY AND EFFECTIVE ENGLISH BY TIGA SERANGKAI USED IN TEACHING ENGLISH IN THE THIRD GRADE STUDENTS OF SMP NEGERI 10 KOTA CIREBON”. - afief fakhruddin (Journal of English Language Learning, 2017)
The research is entitled “A descriptive study on the Usability coherence and cohesion with the curriculum) of some modules. The purposes of this research are (1). To describe the correlation of the used modules of English on sky and Effective English by Tiga Serangkai with the curriculum in teaching English for the third grade students of SMPN 10 Kota cirebon. (2). To figure out how the used modules of English on sky and Effective English by Tiga Serangkai  in teaching English for the third grade students of SMPN 10 Kota Cirebon. (3). To figure out the Teacher’s perception about the Module in teaching English of the third grade students of SMPN 10 Kota Cirebon.This research belongs to descriptive qualitative. the collected data were analyzed by making written description. After conducting the research, the researcher concluded that The modules are not 100% fulfilled the criteria as demanded by 2013 curriculum.  In the teaching and learning, the use of modules is adjusted with the order of basic competences required by the curriculum and also the time allocation. Both modules above are not the only handbooks which are used in the teaching and learning process. The teachers find that using modules in teaching and process is effective although sometimes the units/topics are disorderly arranged.